Effect of statin treatment for familial hypercholesterolaemia on life assurance: results of consecutive surveys in 1990 and 2002 (BMJ Publishing Group, 2004)

(untitled)
One of the concerns often raised about genetic testing is the possibility that a positive result (or even disclosing that the test has been taken) may result in difficulty in obtaining life assurance. Currently the UK insurance industry has declared a moratorium on requiring genetic tests from applicants,1 but since DNA based tests offer a definitive, highly specific diagnosis they are likely eventually to replace less specific clinical diagnostic criteria for many inherited disorders. Early, presymptomatic treatment may increase life expectancy by preventing or reducing the risk of developing the disease or associated complications. However, if life assurance policy premiums do not adequately reflect the reduction in mortality with treatment relatives of affected probands may be deterred from being tested. We examined how life assurance companies have responded to the improvement in the prognosis of heterozygous familial hypercholesterolaemia with statin treatment.2